PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL GOOGLE CLASSROOM PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MTS YAKPI WASILATUL HUDA - Fitriyani Kosasih; Rikha Destya Rahmadanti; Rizki Akbar Mubaroq Azhar; Aris Warisman; Ali Fakhri Amrullah; Muhammad Bisri Syamsuri; Moch Ya’qub Sulaeman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on developing digital learning media by utilizing Google Classroom in Islamic Religious Education subjects at MTs Yakpi Wasilatul Huda. The background to this study is based on conditions where the use of technology in learning has not been maximized, which has an impact on students' low active involvement. Therefore, learning innovations are needed that are able to create a learning atmosphere that is more interesting, interactive, and in line with current developments. The results of this research show that the application of digital platforms can be a solution to improve the quality of the learning process as well as student learning outcomes. This research applies a Research and Development approach by referring to the stages of the ADDIE model which include analysis, design, development, implementation and evaluation. The research subjects were students in Islamic Religious Education subjects, while the objects developed were digital learning media based on Google Classroom. Data collection was carried out through questionnaires to determine student responses and measure learning outcomes. In addition, a qualitative descriptive approach is used to describe in detail the media development process, its implementation in learning, and students' responses to the use of the media. Research findings show that the media developed is considered suitable for use, practical, and able to support learning effectiveness. Its use has been proven to encourage increased student interest and activity during the learning process, as well as having a positive influence on learning outcomes in various aspects. Apart from that, the use of Google Classroom also makes it easier for teachers to manage learning, deliver material, and carry out evaluations in a more focused and efficient manner.             Keywords: Islamic religious education learning, Google Classroom, student involvement, online learning, educational innovation.